The most important problems facing municipal councils and the methods of solving them - Shamayleh, Ammar Youssef Muhammad (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at demonstrating the most important problems facing municipal councils and the methods of solving them by using the analytical descriptive approach through which the researcher addressed the most important problems facing municipal councils and the methods of solving them، such as rehabilitating the human resources in municipalities and activating surveillance over the municipal councils to enhance their relationship with citizens. The results revealed that some municipalities suffer from a lack in financial resources which، in turn، results in a delay in providing service to citizens as required، in addition to the municipal councils' need for trained and qualified staff، who receive training for the newest methods. The study concluded with a number of recommendations، as follows: The municipal councils have to increase their financial resources by getting their due funding from citizens and activate the role of collectors in obtaining taxes and fees. And Rehabilitating the human staff in municipalities and promoting the level of employees in municipalities. Enhancing the relationship between municipalities and local citizens through popular dialogue and giving citizens the opportunity to participate in the activities of the municipal councils. Enhancing the developmental role by establishing developmental projects that benefit municipalities and local community.
Keywords: municipal councils; local administration; Audit Bureau